Postgraduate education pursuit: Deciding factors of graduating accountancy students in selected Manila Universities - Almeda, Andre Philip B.; Antonio, Micah Angela T.; Asusano, Janna L.; Bulatao, Marie Hazel Y.; Ibrahim, Abdul Wahab B.; Russiana, Christine C.; Sambilay, Christine Jewel D.; Tapiador, Danielle Jena N. 4 0 16; 5
ABSTRACT: This research focused on identifying the factors that influence the decision of graduating Accountancy students in pursuing postgraduate education, a critical step that could significantly impact their future career prospects. The study used descriptive quantitative research design that aims to describe and quantify the characteristics of a specific population or phenomenon. Survey questionnaire were administered, and frequency percentage, z-test, and weighted mean analysis were conducted to assess the results. The study identified the influential factors from the four predetermined key factors that the respondents consider in deciding whether to pursue postgraduate education. These predetermined factors were: (1) better career opportunities and financial upgrade, (2) self- gratification, (3) academe sector venture, and (4) social pressure. The findings revealed that two out of the three influential factors, better career opportunities and financial upgrade and self-gratification factors, exerted a significant influence to a great extent and were categorized within the high influence level on the decision of graduating Accountancy students in pursuing postgraduate education. Additionally, social pressure was found to play a role in shaping their choices. However, the extent to which this factor influenced their decisions was found to vary among individuals and was considered to have a neutral extent and level of influence on the decision to pursue postgraduate education. This research provides valuable insights into the decision-making process of graduating Accountancy students regarding postgraduate education, highlighting the multifaceted nature of their choices. The findings could inform educational institutions, policymakers, and stakeholders in developing strategies and support systems that address the identified factors, ultimately promoting informed decision-making among graduating Accountancy students.
Research Paper: (Bachelor of Science in Accountancy) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2